Association of Frailty and Postoperative Complications With Unplanned Readmissions After Elective Outpatient Surgery - Rothenberg, Kara A. (JAMA Netw Open, 2019)
IMPORTANCE: Ambulatory surgery in geriatric populations is increasingly prevalent. Prior studies have demonstrated the association between frailty and readmissions in the inpatient setting. However, few data exist regarding the association between frailty and readmissions after outpatient procedures. OBJECTIVE: To examine the association between frailty and 30-day unplanned readmissions after elective outpatient surgical procedures as well as the potential mediation of surgical complications. DESIGN, SETTING, AND PARTICIPANTS: In this retrospective cohort study of elective outpatient procedures from 2012 and 2013 in the National Surgical Quality Improvement Program (NSQIP) database, 417 840 patients who underwent elective outpatient procedures were stratified into cohorts of individuals with a length of stay (LOS) of 0 days (LOS = 0) and those with a LOS of 1 or more days (LOS ≥ 1). Statistical analysis was performed from June 1, 2018, to March 31, 2019. EXPOSURE: Frailty, as measured by the Risk Analysis Index. MAIN OUTCOMES AND MEASURES: The main outcome was 30-day unplanned readmission. RESULTS: Of the 417 840 patients in this study, 59.2% were women and unplanned readmission occurred in 2.3% of the cohort overall (LOS = 0, 2.0%; LOS ≥ 1, 3.4%). Frail patients (mean [SD] age, 64.9 [15.5] years) were more likely than nonfrail patients (mean [SD] age, 35.0 [15.8] years) to have an unplanned readmission in both LOS cohorts (LOS = 0, 8.3% vs 1.9%; LOS ≥ 1, 8.5% vs 3.2%; P < .001). Frail patients were also more likely than nonfrail patients to experience complications in both cohorts (LOS = 0, 6.9% vs 2.5%; LOS ≥ 1, 9.8% vs 4.6%; P < .001). In multivariate analysis, frailty doubled the risk of unplanned readmission (LOS = 0: adjusted relative risk [RR], 2.1; 95% CI, 2.0-2.3; LOS ≥ 1: adjusted RR, 1.8; 95% CI, 1.6-2.1). Complications occurred in 3.1% of the entire cohort, and frailty was associated with increased risk of complications (unadjusted RR, 2.6; 95% CI, 2.4-2.8). Mediation analysis confirmed that complications are a significant mediator in the association between frailty and readmissions; however, it also indicated that the association of frailty with readmission was only partially mediated by complications (LOS = 0, 22.8%; LOS ≥ 1, 29.3%). CONCLUSIONS AND RELEVANCE: These findings suggest that frailty is a significant risk factor for unplanned readmission after elective outpatient surgery both independently and when partially mediated through increased complications. Screening for frailty might inform the development of interventions to decrease unplanned readmissions, including those for outpatient procedures.